Injuries in elite‐level women's football—a two‐year prospective study in the Irish Women's National League. (31st October 2021) - Horan, Dan; Blake, Catherine; Hägglund, Martin; Kelly, Seamus; Roe, Mark; Delahunt, Eamonn
Abstract : We investigated the pattern of injuries in elite‐level women's football in Ireland, during a two‐season prospective injury surveillance study in the Women's National League (WNL). Seven out of the eight clubs (271 players) in the WNL were followed prospectively during the 2018 and 2019 seasons. The injury incidence rate in matches (19.2/1000 h) was 7.5 times higher than in training (2.5/1000 h). Players, on average, sustained 0.69 injuries per season (266 injuries/383 player seasons), which equates to 15 time‐loss injuries per season for a squad of 22 players. The majority of the injuries sustained by players were lower extremity injuries (85%), of which, 46% had a non‐contact injury mechanism. Muscle, ligament, and contusion injuries were the most common injury types, while the ankle, knee, and thigh were the most commonly injured body sites. The most common injuries sustained over the two seasons were lateral ankle sprains (13.9%), hamstring strains (12.4%), knee meniscus/cartilage injuries (7.5%), adductor strains (6%), quadriceps strains (4.5%), and ankle contusions (4.5%). The injuries with the highest injury burden were ACL injuries (59 days lost/1000 h), knee meniscus/cartilage injuries (23/1000 h), lateral ankle sprains (21/1000 h), hamstring strains (12/1000 h), MCL sprains (11/1000 h), and quadriceps strains (11/1000 h). There were 8 ACL tears documented over the 2 seasons, which accounted for 28% of all time lost to injury with a mean days lost per injury of 247. We recommend that clubs in the WNL in Ireland should implement injury risk mitigation strategies, with a particular focus on injuries with a high injury burden.